Towards a Computational Effective Paradigm for Image Guided Surgery (IGS) - Aboaba, Abdulfattah A.; Hameed, Shihab A.; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha; Harun, Rahmat H.; Mohd Zain, Nurzaini Rose (2011)

(untitled)
The adoption of minimally invasive method in surgical intervention occasioned by Image Guided Surgery (IGS) / Computer Aided Surgery (CAS) has further enhanced the acceptability of IGS into more areas of surgery such as spinal cord surgery, teleguided surgery, robotic controlled surgery, neuro surgery, and even orthopedic surgery and emergency situations which have hitherto least benefitted in IGS for certain obvious impediments. These achievements notwithstanding, IGS is still tied to the traditional procedure which from the perspective of a computer engineer makes it time consuming and irresponsive to patients’ needs. In this paper, a paradigm for a computational effective IGS is presented focusing on two aspects of the current IGS model which are believed to be the bottleneck for improvement viz: pre-operative planning, and inter-operative guidance. The proposed scheme is promising in that operation involving IGS would be quicker and safer.